Electronic and magnetic properties of Co doped MoS(2) monolayer - Wang, Yiren (Sci Rep, 2016)
First principle calculations are employed to calculate the electronic and magnetic properties of Co doped MoS(2) by considering a variety of defects including all the possible defect complexes. The results indicate that pristine MoS(2) is nonmagnetic. The materials with the existence of S vacancy or Mo vacancy alone are non-magnetic either. Further calculation demonstrates that Co substitution at Mo site leads to spin polarized state. Two substitutional Co(Mo) defects tend to cluster and result in the non-magnetic behaviour. However, the existence of Mo vacancies leads to uniform distribution of Co dopants and it is energy favourable with ferromagnetic coupling, resulting in an intrinsic diluted magnetic semiconductor.